BaHfO3 artificial pinning centres in TFA-MOD-derived YBCO and GdBCO thin films. (25th September 2015) - Erbe, M; Hänisch, J; Hühne, R; Freudenberg, T; Kirchner, A; Molina-Luna, L; Damm, C; Van Tendeloo, G; Kaskel, S; Schultz, L; Holzapfel, B
Abstract: Chemical solution deposition (CSD) is a promising way to realize RE Ba2 Cu3 O7− x ( RE BCO; RE = rare earth (here Y, Gd))-coated conductors with high performance in applied magnetic fields. However, the preparation process contains numerous parameters which need to be tuned to achieve high-quality films. Therefore, we investigated the growth of RE BCO thin films containing nanometre-scale BaHfO3 (BHO) particles as pinning centres for magnetic flux lines, with emphasis on the influence of crystallization temperature and substrate on the microstructure and superconductivity. Conductivity, microscopy and x-ray investigations show an enhanced performance of BHO nano-composites in comparison to pristine RE BCO. Further, those measurements reveal the superiority of GdBCO to YBCO—e.g. by inductive critical current densities, J c, at self-field and 77 K. YBCO is outperformed by more than 1 MA cm −2 with J c values of up to 5.0 MA cm −2 for 265 nm thick layers of GdBCO(BHO) on lanthanum aluminate. Transport in-field J c measurements demonstrate high pinning force maxima of around 4 GN m −3 for YBCO(BHO) and GdBCO(BHO). However, the irreversibility fields are appreciably higher for GdBCO. The critical temperature was not significantly reduced upon BHO addition to both YBCO and GdBCO, indicating a low tendency for Hf diffusion into the RE BCO matrix. Angular-dependent J c measurements show a reduction of the anisotropy in the same order of magnitude for both RE BCO compounds. Theoretical models suggest that more than one sort of pinning centre is active in all CSD films.